AUTHENTIC ASSESSMENT OF SPEAKING SKILL IN EFL CLASS: AN ANALYSIS ON ENGLISH TEACHERS’ ASSESSMENT PROCESS - Siti Maysuroh; Zahratul Fikni; Astrid Dwimaulani; Khaerunnisa Miraja (UIBU, 2023)
The objectives of this study are to find out and determine the dominant type of authentic assessment used by teachers, the activity of authentic assessment implemented by teachers, the advantages and disadvantages of using authentic assessment in speaking class.This study used qualitative methods which employed interview, observation, and documents to collect the data. Using the purposive sampling technique, three English teachers at MA NW Perian under Yayasan Pondok Pesantren Pendidikan Darul Muttaqien (YP3DM) NWDI Perian were chosen as the participants of the study. The results of this research showed that (1) the dominant type of authentic assessment used in assessing speaking was performance based assessment; (2) the dominant authentic assessment activities used in assessing speaking were discussion, role-play and debate activity; (3) all of the English teachers agreed that using authentic assessment helped their students demonstrate and perform their true abilities without cheating; and (4) the most disadvantages felt by teachers in implementing authentic assessment in speaking class is that it consumes a lot of time because the teacher must complete the assessment everyday in every activity.